Creative Thinking And Collaboration Skills: Improved Learning With The CORE Model Of Biology Subjects - haka, nukhbatul bidayati; Arifiana, Mifta; Ningrum, Mivtha Citra; Astuti, Yuni; Hidayah, Nur (Phenomenon : Jurnal Pendidikan MIPA, 2022)
This study aims to determine the improvement of creative thinking skills and collaboration skills by using the Connecting, Organizing, Reflecting, and Extending learning model in class XI IPA SMAN 1 Sukoharjo students. This research is quasi-experimental research using a pretest-posttest control group design. Collecting data using creative thinking and collaboration skills tests for students of class XI IPA SMAN 1 Sukoharjo. Samples were taken using the Cluster Random Sampling technique consisting of class XI IPA 2 and XI IPA 3. This study was tested using the MANOVA test. Data analysis shows significant results which means that there is an increase in creative thinking skills and collaboration using the Connecting, Organizing, Reflecting, and Extending learning model I in biology subjects